2013
DOI: 10.1038/ncomms3833
|View full text |Cite
|
Sign up to set email alerts
|

An alternative pathway contributes to phenylalanine biosynthesis in plants via a cytosolic tyrosine:phenylpyruvate aminotransferase

Abstract: Phenylalanine is a vital component of proteins in all living organisms, and in plants is a precursor for thousands of additional metabolites. Animals are incapable of synthesizing phenylalanine and must primarily obtain it directly or indirectly from plants. Although plants can synthesize phenylalanine in plastids through arogenate, the contribution of an alternative pathway via phenylpyruvate, as occurs in most microbes, has not been demonstrated. Here we show that plants also utilize a microbial-like phenylp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
177
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 195 publications
(195 citation statements)
references
References 47 publications
11
177
0
2
Order By: Relevance
“…An amino acid alignment of the predicted protein sequence of the Ab-ArAT proteins and selected homologs indicates that each contains a conserved catalytic lysine that corresponds to residue 270 in Ab-ArAT1, together with conserved residues required for the binding of the pyridoxal-59-phosphate cofactor (Supplemental Figure 3). Ph-PPY-AT was previously shown to be localized in the cytosol rather than the chloroplast (Yoo et al, 2013); similarly, the Ab-ArATs identified in this study are not predicted to be localized to any organelles and lack the typical transit peptides that are characteristic of chloroplast-localized proteins. Phylogenetic analysis of ArATs from Arabidopsis, Atropa, and other Solanaceae, including the fully sequenced tomato and potato genomes, indicated an expansion of the ArAT family in Solanaceae compared with Arabidopsis (Figure 4; Supplemental Table 1) and suggested potential orthologous relationships.…”
Section: Identification Of An Aromatic Amino Acid Aminotransferase Asmentioning
confidence: 76%
See 4 more Smart Citations
“…An amino acid alignment of the predicted protein sequence of the Ab-ArAT proteins and selected homologs indicates that each contains a conserved catalytic lysine that corresponds to residue 270 in Ab-ArAT1, together with conserved residues required for the binding of the pyridoxal-59-phosphate cofactor (Supplemental Figure 3). Ph-PPY-AT was previously shown to be localized in the cytosol rather than the chloroplast (Yoo et al, 2013); similarly, the Ab-ArATs identified in this study are not predicted to be localized to any organelles and lack the typical transit peptides that are characteristic of chloroplast-localized proteins. Phylogenetic analysis of ArATs from Arabidopsis, Atropa, and other Solanaceae, including the fully sequenced tomato and potato genomes, indicated an expansion of the ArAT family in Solanaceae compared with Arabidopsis (Figure 4; Supplemental Table 1) and suggested potential orthologous relationships.…”
Section: Identification Of An Aromatic Amino Acid Aminotransferase Asmentioning
confidence: 76%
“…However, plant genomes have retained multiple ArATs that likely utilize L-Phe and L-Tyr as substrates but, like Ab-ArAT4, are not predicted to be plastid localized. Recently, a petunia ArAT, Ph-PPY-AT, was shown to be localized to the cytoplasm and able to directly catalyze the formation of L-Phe from phenylpyruvate using L-Tyr as the amino donor, yielding 4-HPP as a by-product (Yoo et al, 2013). This reaction is analogous to the formation of L-Phe in bacteria and demonstrates the existence of a second, direct, extraplastidic route to L-Phe biosynthesis in plants and led to a proposed role for Ph-PPY-AT in modulating aromatic amino acid homeostasis (Whitaker et al, 1981;Fischer et al, 1993;Yoo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations